Fatahillah and the Foundations of Islamic Education in Banten: A Historiographical and Sufi Study of the 16th Century - Komariah, Nining Syamsi; Falahudin, Falahudin (Khalifah : Jurnal Pendidikan Nusantara, 2025)
This study aims to examine the contribution of Fatahillah in pioneering Islamic education in the Banten region through a critical historiography and grounded theory approach. Historically, Fatahillah has been primarily recognized as a military commander who captured Sunda Kelapa, while his role in establishing intellectual and spiritual institutions among coastal communities has been largely overlooked in mainstream historical narratives. Based on literature review, field interviews, and site observations, this research reveals that Fatahillah laid the foundation for Islamic education through pesantren (Islamic boarding schools), halaqah (study circles), and Sufi-based teachings. His educational efforts served not only as a means of transmitting knowledge but also as a transformative force for cultural, social, and ideological change in the post-Islamization society. This study further argues that colonial historiography has marginalized Fatahillah’s intellectual legacy, highlighting the need for a more just and contextual reconstruction of historical narratives. The findings contribute significantly to the mapping of the roots of Islamic education in the Nusantara, particularly in the western part of Java.